MENAKAR JALUR PENDIDIKAN LUAR SEKOLAH: MEMUNCULKAN ASA DI ERA OTONOMI DAERAH - Ulum, M Miftahul (IAIN Ponorogo, 2011)
Low Human Resources we are not separated from the low level of public education, especially at school age. The low quality of human resources is caused by many things, such as the inability of school-age children to continue their education to higher education, as a result of poverty is wrapped around family life, or could have been caused by the dropout rate, the same is caused by economic factors. Therefore, an optimistic attitude necessary to be able to raise these human resources. One of the pillars which can not be overlooked is through non-formal education, or better known outside of school education (PLS). Government through the spirit of regional autonomy shall move the non-formal educational programs such as Law No. 20 on National Education System candidly and explicitly states that non-formal education will continue to be cultivated within the framework to create community-based education, and government share responsibility sustainability of non-formal education as an effort to complete the 9-year compulsory education.Â ÙÙØ§ ÙÙØµÙ Ø¨ÙÙ Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© Ø§ÙÙ ÙØ®ÙØ¶Ø© ÙØÙ Ù Ù ØªØ¯ÙÙ Ù Ø³ØªÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§Ù Ø ÙØ®Ø§ØµØ© ÙÙ Ø³Ù Ø§ÙÙ Ø¯Ø±Ø³Ø©. ÙÙØªØ³Ø¨Ø¨ Ø§ÙØ®ÙØ§Ø¶ Ø¬ÙØ¯Ø© Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© Ù Ù Ø®ÙØ§Ù Ø§ÙØ¹Ø¯ÙØ¯ Ù Ù Ø§ÙØ£Ø´ÙØ§Ø¡Ø Ù Ø«Ù Ø¹Ø¯Ù ÙØ¯Ø±Ø© Ø§ÙØ£Ø·ÙØ§Ù ÙÙ Ø³Ù Ø§ÙÙ Ø¯Ø±Ø³Ø© ÙÙ ÙØ§ØµÙØ© ØªØ¹ÙÙÙ ÙÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙØ ÙØªÙØ¬Ø© ÙØ§ÙØªÙØ§Ù Ø§ÙÙÙØ± ØÙÙ ØÙØ§Ø© Ø§ÙØ£Ø³Ø±Ø© Ø Ø£Ù ÙÙ ÙÙ Ø£Ù ÙÙÙÙ ÙØ§Ø¬Ù Ø§ Ø¹Ù Ù Ø¹Ø¯Ù Ø§ÙØªØ³Ø±Ø¨ Ù Ù Ø§ÙÙ Ø¯Ø§Ø±Ø³Ø ÙÙØªØ³Ø¨Ø¨ ÙÙ ÙÙØ³ Ø§ÙØ¹ÙØ§Ù Ù Ø§ÙØ§ÙØªØµØ§Ø¯ÙØ©. ÙÙØ°ÙÙØ ÙÙØ°Ø§ Ù ÙÙÙ Ù ØªÙØ§Ø¦Ù Ø§ÙÙØ§Ø²Ù Ø© ÙØªÙÙÙ ÙØ§Ø¯Ø±Ø© Ø¹ÙÙ Ø±ÙØ¹ ÙØ°Ù Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ©. ÙØ§ØØ¯Ø© Ù Ù Ø§ÙØ±ÙØ§Ø¦Ø² Ø§ÙØªÙ ÙØ§ ÙÙ ÙÙ ØªØ¬Ø§ÙÙÙØ§ ÙÙ Ù Ù Ø®ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§Ù ÙØ Ø£Ù Ø§ÙÙ Ø¹Ø±ÙÙ Ø®Ø§Ø±Ø¬ Ø§ÙÙ Ø¯Ø±Ø³Ø© ÙØ§ÙØªØ¹ÙÙÙ (PLS). ÙØ§ÙØÙÙÙ Ø© Ù Ù Ø®ÙØ§Ù Ø±ÙØ Ø§ÙØÙÙ Ø§ÙØ°Ø§ØªÙ Ø§ÙØ§ÙÙÙÙ Ù ÙÙÙ Ø§ÙØ¨Ø±Ø§Ù Ø¬ ØºÙØ± Ø±Ø³Ù ÙØ© Ø§ÙØªØ¹ÙÙÙ ÙØ© Ù Ø«Ù Ø§ÙÙØ§ÙÙÙ Ø±ÙÙ 20 Ø¨Ø´Ø£Ù ÙØ¸Ø§Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙØ·ÙÙ Ø¨ØµØ±Ø§ØØ© ÙØªÙØµ ØµØ±Ø§ØØ© Ø¹ÙÙ Ø£Ù Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§Ù Ù ÙØ³ØªÙ Ø± ÙØ²Ø±Ø§Ø¹ØªÙØ§ ÙÙ Ø¥Ø·Ø§Ø± ÙØ®ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙØ§Ø¦Ù Ø¹ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø ÙØ§ÙØ§Ø³ØªØ¯Ø§Ù Ø© Ø§ÙØÙÙÙ Ø© Ù Ø³Ø¤ÙÙÙØ© ØØµØ© Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§Ù Ù ÙÙ Ù Ø³Ø¹Ù ÙØ¥ÙÙ Ø§Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¥ÙØ²Ø§Ù Ù 9 Ø³ÙÙØ§Øª